ENDOPHYTIC MICROORGANISMS AND THEIR BIOLOGICALLY ACTIVE METABOLITES - Vakhobova Durdona Sherali qizi; U.K.Yusupov (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Endophytic microorganisms are a diverse group of bacteria, fungi, actinomycetes, and even rare archaea that colonize healthy plant tissues without causing any immediate or overt disease symptoms. These microorganisms establish complex interactions with their host plants, and as a result of coevolution they produce a multitude of secondary metabolites with significant ecological, medical, and industrial importance. The study of endophytic microorganisms and their metabolites has significantly expanded in recent decades due to their enormous potential in pharmaceutical, agricultural, and environmental applications.